2009
DOI: 10.1186/1749-8104-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 is a required downstream effector of Gsx gene function in the embryonic mouse telencephalon

Abstract: Background: The homeobox gene Gsx2 (formerly Gsh2) is known to regulate patterning in the lateral ganglionic eminence (LGE) of the embryonic telencephalon. In its absence, the closely related gene Gsx1 (previously known as Gsh1) can partially compensate in the patterning and differentiation of ventral telencephalic structures, such as the striatum. However, the cellular and molecular mechanisms underlying this compensation remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
87
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 40 publications
8
87
1
Order By: Relevance
“…E18.5) when Sp8-expressing neuroblasts were beginning to reseed the dLGE. This is presumably the result of the Gsx1-and Ascl1/Dlx-led restoration of LGE identity (Toresson and Campbell, 2001;Yun et al, 2003;Wang et al, 2009), which appears to restore neurogenesis and halt ectopic OPC specification. Despite this apparent normalization of VZ progenitors, these transiently generated Gsx2-derived OPCs migrate from the SVZ into the adjacent cerebral cortex and expand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E18.5) when Sp8-expressing neuroblasts were beginning to reseed the dLGE. This is presumably the result of the Gsx1-and Ascl1/Dlx-led restoration of LGE identity (Toresson and Campbell, 2001;Yun et al, 2003;Wang et al, 2009), which appears to restore neurogenesis and halt ectopic OPC specification. Despite this apparent normalization of VZ progenitors, these transiently generated Gsx2-derived OPCs migrate from the SVZ into the adjacent cerebral cortex and expand.…”
Section: Discussionmentioning
confidence: 99%
“…2F), suggesting that they are early OPCs arising from mutant dLGE progenitors. At later stages of embryogenesis the reduced neurogenesis and altered molecular specification in the Gsx2 mutant LGE begins to recover, largely because of the dorsal expansion of Gsx1, and return of Ascl1 and Dlx expression to LGE progenitors (Toresson and Campbell, 2001;Yun et al, 2003;Wang et al, 2009). Thus, we next examined mutant LGE progenitors at E18.5 and found that the ectopic clump of Olig2-positive cells in the dLGE SVZ was no longer obvious ( Fig.…”
Section: Transient Increase In Opc Specification In the Gsx2 Mutant Lgementioning
confidence: 99%
“…It must be, therefore, that other factors can substitute for the absence of Gsx1 in driving the differentiation of LGE progenitors. In this respect, Ascl1 (Mash1), which is known to play an important role in LGE progenitor maturation (38,39), is required for the partial compensatory role of Gsx1 in the Gsx2 mutant telencephalon (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific cellular expression of Gsx1 protein has not been described due to the lack of a well-characterized antibody. Our previous study found that Gsx1, as detected by Gsx1/2 antibody (12), is expressed by a subset of progenitors in the Gsx2 mutant LGE, which are concentrated basally at the VZ/SVZ boundary (16). Using Gsx1-EGFP BAC transgenic mice (together with the Gsx1/2 antibody), we show here that, even in wild-type embryos, Gsx1-expressing progenitors of the vLGE and MGE appear to be clustered at the VZ/SVZ boundary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation